Biosurfactant from Streptomyces zaomyceticus HUS20 isolated from the Indian Himalayan Region (IHR) and its antibacterial activity - Kishorekumar, A.; Radhakrishnan, M.; Manigundan, K.; Ranjani, S.; Thenmozhli, G. S.; Gopikrishnan, V.; Anita, P.; Soytong, K. (My University, 2025)
Actinobacteria, which are known to synthesize bioactive molecules with significant industrial and medicinal applications. In order to assess the possibility for producing biosurfactant (BS), this study identified culturable actinobacteria from the high-altitude soils of Drama Valley, Dugtu Village in the Indian Himalayan Region (IHR). Actinobacteria were isolated from pre-treated soil samples using nutrient agar, starch casein nitrate agar, and actinomycetes isolation agar, which were enhanced with 1% crude oil. Using the haemolytic assay, oil displacement test, emulsification activity, drop collapse assay, and penetration assay, morphologically different colonies were proved for the production of BS. In this study, a promising biosurfactant-producing strain, strain HUS20 showed considerable emulsification index (65%) and a 30 mm zone in the oil displacement test. Using 16S rRNA sequencing, the strain HUS20 was shown to be 100% identical to Streptomyces zaomyceticus (GenBank accession: OQ996835.1). in HR LC MS analysis, the crude biosurfactant extract showed the presence of more than 164 metabolites. Additionally, the crude biosurfactant demonstrated strong antibacterial action against foodborne pathogens, with Bacillus cereus showing the greatest suppression (24 mm zone at 100 mg/ml). The potential of actinobacteria from harsh Himalayan habitats as a useful resource for the synthesis of biosurfactants is highlighted by this work. Streptomyces zaomyceticus HUS20 is found to be promising strain for isolation of potential biosurfactant molecule.
Keywords: Actinobacteria; Biosurfactant (BS); HR-LC-MS; Indian Himalayan Region (IHR); Streptomyces zaomyceticus